Insights into imprinting from parent-of-origin phased methylomes and transcriptomes. (November 2018) - Zink, Florian; Magnusdottir, Droplaug; Magnusson, Olafur; Walker, Nicolas; Morris, Tiffany; Sigurdsson, Asgeir; Halldorsson, Gisli; Gudjonsson, Sigurjon; Melsted, Pall; Ingimundardottir, Helga; Kristmundsdottir, Snædis; Alexandersson, Kristjan; et al.
Abstract Imprinting is the preferential expression of one parental allele over the other. It is controlled primarily through differential methylation of cytosine at CpG dinucleotides. Here we combine 285 methylomes and 11, 617 transcriptomes from peripheral blood samples with parent-of-origin phased haplotypes, to produce a new map of imprinted methylation and gene expression patterns across the human genome. We demonstrate how imprinted methylation is a continuous rather than a binary characteristic. We describe at high resolution the parent-of-origin methylation pattern at the 15q11.2 Prader–Willi/Angelman syndrome locus, with nearly confluent stochastic paternal methylation punctuated by 'spikes' of maternal methylation. We find examples of polymorphic imprinted methylation unrelated (at VTRNA2-1 and PARD6G) or related (at CHRNE) to nearby SNP genotypes. We observe RNA isoform-specific imprinted expression patterns suggestive of a methylation-sensitive transcriptional elongation block. Finally, we gain new insights into parent-of-origin-specific effects on phenotypes at the DLK1/MEG3 and GNAS loci. Two hundred and eighty-five methylomes and 11, 617 transcriptomes from peripheral blood samples with parent-of-origin-phased haplotypes produce a new map of imprinted methylation and gene expression patterns across the human genome.